Screening of yeast isolates for the biocontrol of Sclerotium rolfsii - NURHALIMAH NURHALIMAH; ANTON MUHIBUDDIN; MUHAMMAD AKHID SYIB’LI (Society for Indonesian Biodiversity, 2022)
Abstract. Nurhalimah, Muhibuddin A, Syib’li MA. 2022. Screening of yeast isolates for the biocontrol of Sclerotium rolfsii. Biodiversitas 23: 3820-3826. Sclerotium rolfsii is a fungal pathogen that can reduce peanut production. Biological control with yeast antagonist offers an environment friendly control for this pathogen. The aim of this study was to isolate and identify yeast antagonists, and to study their antagonistic mechanism and potential to control the peanut disease caused by S. rolfsii. The study was conducted from October 2020 to May 2021. The study consisted of four stages: isolation and identification of yeasts, yeasts antagonist testing against S. rolfsii, molecular identification of yeast NH4, and scanning electron microscope observation of NH4 against S. rolfsii. Based on the research, four different yeast isolates were isolated, identified, and found able to be developed as a biological control agent to inhibit the growth of S. rolfsii. Identification showed that NH1 was Saccharomyces sp. with inhibitory percentage of 9,26%, NH2 was Candida sp. with 22,21% inhibition of, NH3 Pichia sp. with 11,11% inhibition of, and NH4 was Wickerhamomyces sp. with an inhibitory percentage of 32,96%. The results of the yeast antagonism mechanism showed that NH1 (Saccharomyces sp.) and NH3 (Pichia sp) had not showed any mechanism while, NH2 (Candida sp.) had a competition and NH4 (Wickerhamomyces sp.) had an antibiosis mechanism. NH4 can suppress the growth of S. rolfsii by more than 30%, which has been identified as species of Wickerhamomyces sp. (NH4) with 99.84% homology with Wickerhamomyces anomalus CBS 5759 with accession number MH545921.1.